Marketing Thirst - Saleh, Muhammad Surya; Agustiani, Fitri; Pradini, Gagih; Kusumaningrum, Anisa Putri (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
Drinks are an indispensable part of human daily life. Various types of drinks are present to meet various needs and tastes. One of Jakarta's most popular beverage brands today is HAUS, which offers various variants of refreshing drinks. Culinary tourism is one of the tourism concepts that are developing throughout the world. Culinary is also one of the supporting elements that are very important in the success of tourism in a destination. Culinary, especially local culinary, is even able to describe the entire culture of the people in an area. Likewise, in Indonesia's Special Economic Zone (SEZ), the development of local culinary is an opportunity to encourage the development of this region. Drinks are an indispensable part of human daily life. Various types of drinks are present to meet various needs and tastes. One of Jakarta's most popular beverage brands today is HAUS, which offers various variants of refreshing drinks. The purpose of this journal is to understand more deeply the HAUS brand beverage, how to market its integrity, marketing mix or 4P, and STP (Segment, Target, Positioning). Not only that, we also analyzed the SWOT of Albert Humphrey on the HAUS beverage brand.